IMPLEMENTATION OF PROJECT-BASED LEARNING ON STUDENTS' PERCEPTIONS AND UNDERSTANDING OF COMPETENCIES IN CREATIVE PROJECTS AND ENTREPRENEURSHIP SUBJECTS - Widyanarka, Fajar; Anas, M.; Muchson, M. (PUSAT KEWIRAUSAHAAN UNIVERSITAS BALIKPAPAN, 2025)
This study aims to explore the implementation of project-based learning (PjBL) in the Creative Projects and Entrepreneurship subject at SMK Negeri 1 Pagerwojo and students' perceptions of the application of this learning model. The research methods used include a quantitative approach with data collection techniques such as observation, documentation, and student perception questionnaires. The results of the study indicate that PjBL has been implemented systematically through the stages of planning, implementation, monitoring, and evaluation. The Lesson Plan (RPP), teaching modules, guidance sheets, and evaluation formats serve as guidelines for the implementation of learning. In terms of student perceptions, the majority of respondents gave very positive responses, particularly regarding learning motivation, competency understanding, interaction with teachers, time management, learning outcomes, and the suitability of the learning model to the characteristics of the subject. Based on the analysis, more than 40% to 80% of students placed their perceptions in the “Very Good” category. However, there are still some suggestions from students regarding the need to enhance active participation and individual assessment strategies for optimal results. This study recommends that the project-based learning model be maintained and further developed, not only in the Creative Projects and Entrepreneurship subject but also in other productive subjects